2022
DOI: 10.1007/s42991-021-00177-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic identifications challenge our assumptions of physical development and mother–calf associations and separation times: a case study of the North Atlantic right whale (Eubalaena glacialis)

Abstract: While photo-identification is an effective tool to monitor individuals in wild populations, it has limitations. Specifically, it cannot be applied to very young animals before their identifying features have stabilized or to dead, decomposed animals. These shortfalls leave gaps in our understanding of survival, parentage, age structure, physical development, and behavioral variability. Here we report on 13 case studies of North Atlantic right whale, Eubalaena glacialis, calves that required genetics to track t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Satellite telemetry data from a single leopard seal (Hydrurga leptonyx), a species where lactation durations are unconfirmed but speculations range from 10 days to 8 weeks (Southwell et al, 2003), provides preliminary support for a 2-week lactation duration (Kienle et al, 2022). In North Atlantic right whales, the use of genetic identification revealed that at least two calves never observed on the foraging grounds with their mothers survived, indicating successful weaning as early as 7.5 to 8.0 months of age on the northbound migration (Hamilton et al, 2022) A particular challenge in estimating total lactation costs is that there is a high degree of intraspecific variation in lactation durations in some species. Bioenergetic models and associated outputs, such as dynamic models estimating reproductive parameters, can be sensitive to lactation durations (New et al, 2013).…”
Section: Lactation Durationmentioning
confidence: 94%
See 2 more Smart Citations
“…Satellite telemetry data from a single leopard seal (Hydrurga leptonyx), a species where lactation durations are unconfirmed but speculations range from 10 days to 8 weeks (Southwell et al, 2003), provides preliminary support for a 2-week lactation duration (Kienle et al, 2022). In North Atlantic right whales, the use of genetic identification revealed that at least two calves never observed on the foraging grounds with their mothers survived, indicating successful weaning as early as 7.5 to 8.0 months of age on the northbound migration (Hamilton et al, 2022) A particular challenge in estimating total lactation costs is that there is a high degree of intraspecific variation in lactation durations in some species. Bioenergetic models and associated outputs, such as dynamic models estimating reproductive parameters, can be sensitive to lactation durations (New et al, 2013).…”
Section: Lactation Durationmentioning
confidence: 94%
“…In some cases, this can result in lactation durations that are not well resolved, particularly if the composition of fisheries catches is nonrandom (Kasuya, 1978). Even when direct observations are available, they are often based on associations between an adult female and her presumed calf, which could result in erroneous estimates if they remain associated for reasons other than nursing, are not always together (a common occurrence), or are in fact not a mother-calf pair (Hamilton et al, 2022).…”
Section: Lactation Durationmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability of calf loss ( κ ) was assigned a Beta(2, 8) prior to reflect knowledge that it should be low. The probability of a missed summer calf ( ρ calf ) was assigned a Beta(5, 445) prior consistent with the observation of 5 calves during summer surveys that were without mothers (individuals that could themselves be sighted without a calf, despite calf survival) out of 450 successful calving events during 1990-2019; this informed prior was a necessary approximation given the lack of an alternative approach to modeling summer calf detection (for additional insights, see Hamilton et al (2022)). To improve mixing we used a sum-to-zero approach for the random effects (Ogle and Barber, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Some photographic data remain too challenging for semiautomated photo identification of right whales at this time, such as dead or decomposed animals, those showing only a portion of the body while engaged in a surface active group, or newborns with features that have not yet stabilized (Hamilton et al 2022).…”
Section: Difficult Matchesmentioning
confidence: 99%